Standardization of Pela tourism village homestays and service improvement in accordance with the standards of the Minister of Tourism Number 9 of 2014 - Muhammad Fauzan Noor; Anna Rulia; Said Keliwar (Community Empowerment, 2021)
Tourist visits to Pela Village have increased since it was confirmed as a tourist village by the Regent of Kutai Kartanegara in June 2019 based on River Ecotourism and the development of the Pesut Mahakam Mammal Ecosystem. The village managed by the Tourism Awareness Group (POKDARWIS) coordinates with the local community to provide services for their house rooms to be used as homestays. However, only two houses are willing and most often used while the others are still not standardized. This service activity aims to assist the Pela tourism village in preparing homestays to comply with the standardization of the Minister of Tourism Number 9 of 2014. The method used is training on the urgency of standardized homestays from the elements of product, service and management. Then, the activity was continued by homes visiting in turn to see the suitability of homestay standards, by providing assessments as well as input and suggestions in accordance with existing standards. This service has resulted in 9 houses that are ready to be used as homestays.